Sanksi Kasepekang Dalam Hukum Adat Bali - I Ketut Sukadana; Diah Gayatri Sudibya; Ni Made Sukaryati Karma (Kertha Wicaksana, 2021)
Traditional villages in Bali as now regulated through the Bali Provincial Regulation Number 4 of 2019, have the same government system. Activities carried out in traditional villages cover the custom and religious fields, where a traditional village in Bali has its own customary rules which are outlined in the village awig-awig. Customary village government is autonomous, meaning that each customary village has its own rules which only apply to the residents of the village / banjar concerned. In general, the rules contained in awig-awig must not at all conflict with the prevailing regulations at the national or regional levels. But in reality there are still awig-awig in some traditional villages that contain sanctions that are no longer suitable to the times, such as still applying the Kasepekang customary sanction, namely exclusion from the association of living together. The exclusion of members of the community is not half-hearted, and some have even closed off access to the outside of their home yard. The problems examined in this study: (1) the regulation of sanctions in Balinese customary law, and (2) the factors that become the reasons for the implementation of the kasepekang customary sanctions. This type of research is empirical with data collection techniques using interviews with informants. Based on the research results, it can be said that the customary sanctions arrangements are listed in the awig-awig of each customary village, namely indik pamidanda (regarding sanctions); As for the reason that the kasepekang sanction is still being applied in people's lives is because the person concerned is outrageous and difficult to foster, besides this type of sanction is stated in awig-awig so that the prajuru adat (traditional leader) still has a legal basis to apply it.